The Downstream Regulation of Chemokine Receptor Signalling: Implications for Atherosclerosis - Jyoti Patel; Keith M. Channon; Eileen McNeill (Hindawi Limited, 2013)
Heterotrimeric G-protein-coupled receptors (GPCRs) are key mediators of intracellular signalling, control numerous physiological processes, and are one of the largest class of proteins to be pharmacologically targeted. Chemokine-induced macrophage recruitment into the vascular wall is an early pathological event in the progression of atherosclerosis. Leukocyte activation and chemotaxis during cell recruitment are mediated by chemokine ligation of multiple GPCRs. Regulation of GPCR signalling is critical in limiting vascular inflammation and involves interaction with downstream proteins such as GPCR kinases (GRKs), arrestin proteins and regulator of G-protein signalling (RGS) proteins. These have emerged as new mediators of atherogenesis by functioning in internalisation, desensitisation, and signal termination of chemokine receptors. Targeting chemokine signalling through these proteins may provide new strategies to alter atherosclerotic plaque formation and plaque biology.